Cutaneous Manifestations in Patients with Chronic Kidney Disease on Hemodialysis and its Correlation with Renal Function, Dialysis Cycle and Haemoglobin - Pradhan, Manish; Chettri, Gaurav; Rai, Dipa; Paudel, Sagar (Birat Journal of Health Sciences, 2018)
Introduction: Skin is the mirror of an internal disease, including the renal system. Chronic kidney disease presents with variety of skin diseases, which is caused either by kidney disease or by treatment modalities. Objective: To evaluate the revalence of various skin disease in patients with chronic renal disease and relation of various skin diseases with serum creatinine, blood urea, hemoglobin and number of hemodialysis cycle. Methodology: A cross-sectional analytical study was conducted in hundred patients of either sex, aged 18 years and above; with chronic kidney disease (stage V) admitted for dialysis in Nephrology department of Nobel Medical College and teaching hospital, Biratnagar, Nepal. The study groups were evaluated for various skin manifestation and parameters of renal function like blood urea and serum creatinine. Results: Among the total patients (n=100), 84 patients presented with complain of skin manifestation but on detail examination 97 patients had at least one skin disease. The causes leading to chronic kidney disease were found to be hypertension 58%, diabetes mellitus 49%, IgA nephropathy 7%, systemic lupus erythematosus 7% and glomerulonephritis 4%. Xerosis was the commonest skin disease encountered in these patients amounting to 71% among which 43 were hypertensive and 34 were diabetic. Xerosis was followed by pruritus (62%), pallor (54%), mucosal changes (39%), skin infection (36%), hair changes (34%), pigmentation (33%) and nail changes (29%). Serum creatinine showed statistically significant association with pruritus ( =0.030) and pigmentation ( =0.010), similarly blood urea showed significant association with pruritus ( =0.001). Similarly, number of dialysis cycle showed significant association with pigmentation of skin ( =<0.001). Conclusion: Chronic kidney disease is associated with variety of skin diseases. The commonest were xerosis and pruritus. Early detection and appropriate intervention can relieve and decrease suffering. BJHS 2018;3(2)6:468-474.